Impacts of climate change versus land use change on recent Lijiang River flood regime, South China - Dai, Junfeng; Rad, Saeed; Xu, Jingxuan; Pen, Sytharith; Gan, Lei; Chen, Xiaobing; Yu, ChenWenjiong; Zhang, Shuaipu (Tecnología y ciencias del agua, 2021)
Rapid development synchronized with human-caused climate change, have induced several critical environmental challenges in south China. The current work compares the drivers of hydrological flux changes and flood reoccurrences in the Lijiang River basin. Using satellite images, SWAT and HEC-HMS models, Mann-Kendall and Minitab trend tests, analysis on climatic as well as land use/land cover changes (LULCC) were carried out statistically. Daily hydrometeorological data were quantitatively analyzed during 1967-2016 for fluctuation regime and pattern recognition. A more uneven rainfall pattern in recent decades was found aligned with the excessive runoff. The average temperature and relative humidity have continuously increased by 0.96 °C and decreased by 3 %, respectively during the last 50 years. Land use maps were used to observe the watershed land conversion during pre/post-development via GIS. Although up to 76 % increase in urbanized areas was detected; however, only 0.6 % of LULCC was noticed which had a 0.1 % change in the curve number (CN) in the entire watershed. HEC-HMS model results revealed negligible changes of hydrographs with and without LULCC. Our study suggests that the main cause of the recent flood upward trends is ascribed to the precipitation pattern changes as a response to global warming, rather than LULCC. The result is underpinned by a rise in the extreme intensity rainfall event’s frequency. The need for sustainable development to adapt to the new situation was supported by the outcomes.